Tujuan penelitian ini adalah untuk mengetahui 1) sejauh mana kemampuan menganalisis pemecahan masalah pada soal cerita peserta didik di SD Negeri Banyuanyar 3 Surakarta, 2) faktor yang mempengaruhi kemampuan pemecahan masalah pada soal cerita matematika peserta didik di SD Negeri Banyuanyar 3 Surakarta. Jenis penelitian yang digunakan ialah penelitian deskriptif kualitatif dengan strategi studi kasus. Hasil penelitian ini yaitu: (1) Peserta didik dengan kategori tinggi mampu menyelesaikan tes so - Anisa Julia Prawesti; Agustinus Roedy Koesdyantho; Ratna Widyaningrum (FKIP, PGSD, Universitas Slamet Riyadi, 2021)
The purpose of this study is: 1) Analyzing the assessment stages of learning outcomes in Online Learning. 2) Describing the obstacles faced by teachers in assessing participants' learning outcomes in Online Learning. 3) Knowing the teacher's efforts in optimizing the assessment of learners' learning outcomes in Online Learning. The research method used is qualitative descriptive research. The results of the research obtained are 1) The assessment stage of learning outcomes consists of planning, implementation, and follow-up, 2) Constraints in the assessment of students' learning outcomes, namely teachers are less able to assess the objectivity of learners, constrained by networking and technical constraints, and the need for the cooperation of teachers, students, and parents in carrying out online learning. 3) The efforts that have been made by teachers are sorting out KI and KD, learning goals, and conducting meaningful assessments with the situation of students conditions, doing home visits, approaching parents, and rewarding the efforts and results obtained by students